'Micro-Tina' and 'Micro-Gemma' Miniature Dwarf Tomatoes - John W. Scott; Brent K. Harbaugh; E. A. Baldwin (EDIS, 2005)
'Micro-Tina' is a red-fruited, miniature dwarf tomato (Lycopersicon esculentum Mill.) cultivar of a type similar to 'Micro-Tom' (Scott and Harbaugh, 1989) but with sweeter flavor. 'Micro-Gemma' is a gold-fruited, miniature dwarf with superior flavor to that of 'Micro-Gold' (Scott and Harbaugh, 1995). These companion releases provide tomato cultivars that are genetically smaller (plant, fruit, leaves, and stems) than are normal dwarf cultivars. They can be grown in small pots, on window sills, or in small hanging baskets. They provide a well-proportioned plant ideally suited to commercial growing, shipping, and marketing because of their small size and light weight. This is document HS986, a publication of the Horticultural Sciences Department, Florida Cooperative Extension Service, IFAS, University of Florida. Publication date: June 2004.